PERJALANAN RONGGENG TAYUB DI PRIANGAN - Toto Sudarto (Greget, 2015)
A study of ronggeng viewed from the historical perspective interested. In fact it has beeninfluenced by a pre-historical period where human believe in super natural. Peopole in the prehistoric period connected the rituals with dance atraction for their own significance. The ronggengincluded as a dance figure connected to the rituals because of its originally from the saman danceand it similiar to the dance of woman priest. It remains us to the function of ‘catalyst’to theancestors. Ronggeng was symbols of recovery rites in the human believe. Ronggeng was alsosymbol of a fertility rites in the human believe in addition to the relationship of its function hasbeen influenced by the Dongson’s culture for the mostly Southeast Asia societies where theybelieve on the Goddess of Rice. Therefore the information of ronggeng has been wrote in Indian’sliterature and sculpture or relief panels of the temple. Eventually the ronggeng is identicallywith fertility rites because of its relation to the Sri Devi and in other side is its atraction has alsoviewed as laisure among the aristocrats. In the Islam’s period where performing arts used to be away of dakwah, so that the ronggeng status in herent with the sufi a manifestation of ma’rifat’sways, where the human assumted to their God. In feudalism feriod of Priangan the ronggeng as apersonal symbol. During this period ibing keurseus appeared as a new version of tayuban bystressing on aesthetic movement appearance. At last the ronggeng unappeared because of its ignorance to the etic norm of religion.Keywords: the ronggeng, continuities, the changing function.